2007
DOI: 10.1080/07408170701592515
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous optimization of [Xbar] control chart and age-based preventive maintenance policies under an economic objective

Abstract: The economic design of control charts and the optimization of preventive maintenance policies have separately received a tremendous amount of attention in the quality and reliability literature over the years in an attempt to reduce the costs associated with operating manufacturing processes. Not until recently has the proposal been made to integrate these two fields and utilize the relationship between quality and equipment performance to improve the productivity of a manufacturing process. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Cassady et al (2000) studied X-chart in conjunction with an age-based preventive maintenance policy. Yeung et al (2008) modified the model suggested by Cassady et al (2000) for using an X-chart to monitor the output of the production process and to determine when to perform corrective, condition-based maintenance so as to optimise the sample size, control chart parameters, and time to interval for performing PM. Rahim and Ben-Daya (2001) provided an overview of the literature dealing with integrated models for production, quality, and maintenance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cassady et al (2000) studied X-chart in conjunction with an age-based preventive maintenance policy. Yeung et al (2008) modified the model suggested by Cassady et al (2000) for using an X-chart to monitor the output of the production process and to determine when to perform corrective, condition-based maintenance so as to optimise the sample size, control chart parameters, and time to interval for performing PM. Rahim and Ben-Daya (2001) provided an overview of the literature dealing with integrated models for production, quality, and maintenance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They present a model using age-replacement where a machine is taken out for preventive maintenance and replaced by a standby one if its age reaches a certain value. Yeung et al 8 extend the initial preliminary investigation of integrating the economic design of control charts and the optimization of preventive maintenance policies of using anX chart in conjunction with an age-replacement preventive maintenance policy. They formulate a partially observable, discrete-time Markov decision process in order to obtain the near-optimal combined preventive maintenance/statistical process control policy that minimizes the costs associated with maintenance, sampling, and poor quality.…”
Section: Introductionmentioning
confidence: 98%
“…Pandey, Kulkarni, and Vrat (2010) contend that a relationship exists between maintenance management and SPC. Some studies on the integration of maintenance management and SPC can be found in Yeung, Cassady, and Schneider (2007), Radhoui, Rezg, and Chelbi (2009), Panagiotidou and Tagaras (2008, Wang (2012), and so on.…”
Section: Introductionmentioning
confidence: 99%